Squamous Cell Carcinoma Arising in a Mature Cystic Teratoma of the Ovary: A Case Report - Lama, Poonam; Pariyar, Jitendra; Thapa, Bimal Kumar; Chitrakar, Neer Shobha; Shrestha, Isha; Maharjan, Rima; Joshi, Arun Prasad; Maharjan, Pabitra; Neupane, Sameer; Koirala, Srijana; et al. (Nepalese Journal of Cancer, 2019)
Mature cystic teratomas account for about 30-45% of all ovarian tumors. Malignant transformation in these tumors is a rare event, occurring in only 0.17-2% of cases, with squamous cell carcinoma being the most common type. As there are no specific signs and symptoms to suggest malignancy in dermoid cyst, it is difficult to predict, and most cases are diagnosed postoperatively. We report a 55-year-old postmenopausal lady who presented with the complaint of pain in abdomen and abdominal distension for four months and a large complex abdomino-pelvic mass evident clinically and radiologically. Final histopathology was reported as malignant transformation in mature cystic teratoma. The patient was assigned to squamous cell carcinoma of the ovary arising in a mature cystic teratoma, surgical stage IIC. In view of the poor prognosis, adjuvant chemotherapy was given.